10 years of 1:1 taping in Belgium — A selection of murder cases involving fibre examination. Issue 1 (January 2016) - De Wael, K.; Lepot, L.; Lunstroot, K.; Gason, F.
Abstract: Since 2002, the 1:1 tape lifting technique on murder victims has been introduced in Belgium. Thirty-six murder cases for which a fibre examination was carried out in our laboratory between 2002 and 2012 are reviewed. These cases all involved the collection of microtraces on 39 victims using a 1:1 taping or similar technique, called semi 1:1 taping. The degree of "positive outcomes" for investigative and comparative fibre cases is high. Especially in cases where the modus operandi of suspects had to be verified, the examination of the 1:1 tape lifting led to very useful fibre results. The findings from some of these fibre cases are used to illustrate the advantages, drawbacks and points of interest of the two collection techniques. These are also compared with the zonal taping technique, another microtrace collection technique applied on victims at the crime scene. Highlights: Literature review on 1:1 taping and zonal taping Review of fibre examinations in 36 murder cases in which 1:1 taping was used High percentage of fibre examinations with "positive outcome" Useful findings for cases in which 1:1 taping is used to verify statements of suspect Advantages, inconveniences and points of interest are discussed using case examples